(untitled) (Bangladesh Critical Care Journal, 2021)
Background: Disorders of sodium (Na+) and water homeostasis are common in hospitalized patients particularly in Intensive Care Unit (ICU). Irrespective of the etiology it is associated with worse outcome and increase length of ICU stay. Objectives: Objective of the current study is to determine the frequency of hyponatremia and its association with the outcome of critically ill Patients admitted in the Department of Critical Care Medicine, BIRDEM General Hospital. Methods: This prospective observational cross-sectional study was taken place in department of Critical Care Medicine for a period of one year from 1st July, 2017 to 30th June, 2018. Consecutive 296 critically ill patients during this time period were included in this study according to selection criteria. Data were collected in preformed data collection sheet and analyzed by the statistical packages for social science (SPSS) software (version 20.0) Results: In this study total 296 patients after fulfilling the inclusion criteria were selected as study participants. The mean age of the patients was 62.21±12.974 years and there were61.5% male and 38.5% female. Among male patients 39.6% had hyponatremia and among female patients 44.9% (p=0.09). Overall frequency of hyponatremia was 41.2%. Majority of the patients presented with respiratory distress (61.5%), altered level of consciousness (33.4%), hypotension (30%) and fever (18.9%). DM (90.5%), HTN (75.5%) and CKD (50.5%) were the most frequent comorbidities present among the participants. Most of the hyponatremic patients were euvolemic (50.00%). Mean APACHE ll score among hyponatremic patients was significantly high (p= 0.001) moreover, hyponatremic patients required more mechanical support (p= 0.001).Duration of ICU stay was not related to severity of baseline hyponatremia during admission (p= 0.08)). In addition, outcome of the patients also depends on the overall incidence of hyponatremia and degree of hyponatremia (p<0.05 in both cases). Conclusion: More than one-third of critically ill patients had hyponatremia and it was related to poor outcome of the critically ill patients. Bangladesh Crit Care J September 2021; 9 (2): 68-73